Plasma brain-related biomarkers and potential therapeutic targets in pediatric ECMO - Sue J. Hong; Bradley J. De Souza; Kristen K. Penberthy; Lisa Hwang; David E. Procaccini; John N. Kheir; Melania M. Bembea (Neurotherapeutics)
Extracorporeal membrane oxygenation (ECMO) is a technique used to support severe cardiopulmonary failure. Its potential life-saving benefits are tempered by the significant risk for acute brain injury (ABI), from both primary pathophysiologic factors and ECMO-related complications through central nervous system cellular injury, blood-brain barrier dysfunction (BBB), systemic inflammation and neuroinflammation, and coagulopathy. Plasma biomarkers are an emerging tool used to stratify risk for and diagnose ABI, and prognosticate neurofunctional outcomes. Components of the neurovascular unit have been rational targets for this inquiry in ECMO. Central nervous system (CNS) neuronal and astroglial cellular-derived neuron-specific enolase (NSE), tau, glial fibrillary acidic protein (GFAP) and S100β elevations have been detected in ABI and are associated with poorer outcomes. Evidence of BBB breakdown through peripheral blood detection of CNS cellular components NSE, GFAP, and S100β, as well as evidence of elevated BBB components vWF and PDGFRβ are associated with higher mortality and worse neurofunctional outcomes. Higher concentrations of pro-inflammatory cytokines (IL-1β, IL-6, IFN-γ, TNF-α) are associated with abnormal neuroimaging, and proteomic expression panels reveal different coagulation and inflammatory responses. Abnormal coagulation profiles are common in ECMO with ongoing studies attempting to describe specific abnormalities either being causal or associated with neurologic outcomes; vWF has shown some promise. Understanding these mechanisms of injury through biomarker analysis supports potential neuroprotective strategies such as individualized blood pressure targets, judicious hypercarbia and hypoxemia correction, and immunomodulation (inhaled hydrogen and N-acetylcysteine). Further research continues to elucidate the role of biomarkers as predictors, prognosticators, and therapeutic targets.